2020
DOI: 10.48550/arxiv.2008.10792
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anisotropy as a diagnostic test for distinct tensor network wavefunctions of integer and half-integer spin Kitaev quantum spin liquids

Hyun-Yong Lee,
Takafumi Suzuki,
Yong Baek Kim
et al.

Abstract: Contrasting ground states of quantum magnets with the integer and half-integer spin moments are the manifestation of many-body quantum interference effects. In this work, we investigate the distinct nature of the integer and half-integer spin quantum spin liquids in the framework of the Kitaevs model on the honeycomb lattice. The models with arbitrary spin quantum numbers are not exactly solvable in contrast to the well-known quantum spin liquid solution of the spin-1/2 system. We use the tensor network wavefu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Interestingly, this is consistent with the argument put forth in Ref. [12] that the integer-spin Kitaev model has bosonic exciations instead of Majorana fermions, indicating that the different sign structures of the integer and halfinteger spin LG projectors may faithfully describe the distinct nature of the integer and half-integer spin Kitaev models [21].…”
supporting
confidence: 90%
See 4 more Smart Citations
“…Interestingly, this is consistent with the argument put forth in Ref. [12] that the integer-spin Kitaev model has bosonic exciations instead of Majorana fermions, indicating that the different sign structures of the integer and halfinteger spin LG projectors may faithfully describe the distinct nature of the integer and half-integer spin Kitaev models [21].…”
supporting
confidence: 90%
“…We identify the nature of Z 2 QSL of the spin-1 Kitaev model by evaluating the virtual order parameters naturally defined in Z 2 -invariant PEPS [28]. Due to the fundamental distinction between the integer and half-integer LG projector [21], we found that in contrast to the dispersive Majorana excitation in S = 1/2, the spin-1 Kitaev model possesses a dispersive charge anyon excitation. Also, the TM spectrum suggests the existence of the charge excitations with a small gap at the Γ,K and K points in the Brillouin zone.…”
mentioning
confidence: 99%
See 3 more Smart Citations